Religion and Politics in Latin America : The Catholic Church in Venezuela & Colombia - Levine, Daniel H. (Book collections on Project MUSE., 2014)
This book explores the transformations in religion in conjunction with political change. Professor Levine suggests, highlights the dynamic and dialectical interaction between religion and politics in general, and addresses the more universal problem of relating thought to action Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books w.